The Role of Familial Trust in the Leader-member Exchange - Štangej, Olga; Škudienė, Vida (Organizations and Markets in Emerging Economies, 2016)
Drawing on the study of micro and small family businesses in a transition economy, this research explores the effects of trust transferred from the family to the business system. Specifically, it examines how the leader’s interpersonal trust in the member affects the quality of the leader-member exchange (LMX) in familial dyads. The results reveal that interpersonal trust has a positive effect on LMX and the degree of this association depends on the leader’s orientation. This relationship is strengthened by the leader’s orientation, however, only in the case when the orientation is family-centric. The moderating effect is not statistically significant when the leader adopts business-centric orientation.
Keywords: family business; trust; leader-member exchange